Utaut factors influencing intention to use social TV among university students - Khoshrouzadeh, Jafar (2020)
Recent research shows that in line with the advent of broadband Internet and more connectivity through online channels and platforms such as social media, social networking sites, and smartphone messengers, TV viewers are involved in several activities including sharing, commenting, recommending, rating, and liking posts while watching TV. Such activities have led to a new concept in TV viewership known as 'Social TV'. As social TV is in its infancy, research on its multifaceted aspects is scant. In the context of Malaysia, the frequency of use, as well as the factors that determine individuals’ intention to use social TV have not been investigated. Thus, the main objective of this study is to determine factors that influence the intention to use and the frequency of social TV usage among Malaysian students. To achieve this, a quantitative research method based on the UTAUT and UTAUT2 model, utilizing a cross-sectional survey was designed. The respondents of the study were 774 students from both the public and private institutions of higher education in Malaysia that were selected through a multi-stage cluster sampling method. A slightly modified Likert scale questionnaire designed and validated by Venkatesh et al. (2012) was adopted to collect data and finally, Pearson’s Correlation and Multiple regression, as well as Structural Equation Modelling (SEM) as an appropriate statistical analysis method run by SmartPLS 3.0, applied to analyze the data.The findings of the study revealed that Malaysian students are involved in several activities including sharing, recommending, rating, and commenting on TV programs from a daily to weekly basis. The findings also showed that student’s expectance toward the usefulness of social TV is among the main factors that positively affect their intention to use it. Students' perceptions of the resources and support available to use social TV also have a positive influence on the usage of social TV among them. Similarly, the price of social TV-related services and applications as well as habits play a key role in student’s intention to use social TV. Additionally, the findings of the study revealed that the influence of hedonic motivation and habit, as well as friends and family encouragement on the intention to use social TV, was more significant among the male students. Besides, the moderation effect of gender on the path relationship between performance expectancy on behavioral intention was supported for the female group. It was also found that older students were more influenced by the provision of amenities such as educational services, etc. In addition, the influence of habit on behavioral intention to use social TV was moderated by age in favor of older students. Also, younger students were found to be more influenced by friends and family when it comes to social TV usage. Furthermore, it was also found that social TV users in the early stages of their experience require more educational materials and tutorials and they are almost influenced by friends and family when it comes to social TV usage. Theoretically, the findings of the current study provide significant contributions to research in the field of computer-mediated communication, social media, and social TV studies. Results from current study can have implications for broadcasters, marketers, mobile app developers, and IPTV service providers practically.